CRISPR Typing Increases the Discriminatory Power of Streptococcus agalactiae Typing Methods - Beauruelle, Clémence; Treluyer, Ludovic; Pastuszka, Adeline; Cochard, Thierry; Lier, Clément; Mereghetti, Laurent; Glaser, Philippe; Poyart, Claire; Lanotte, Philippe (Frontiers in Microbiology, 2021)
We explored the relevance of a CRISPR-based genotyping tool for Streptococcus agalactiae typing and we compared this method to current molecular methods (MLST and capsular typing). To this effect, we developed two CRISPR marker schemes (using 94 or 25 markers respectively). Among the 255 S. agalactiae isolates tested, 229 CRISPR profiles were obtained. The 94 and 25 markers made it possible to efficiently separate isolates with a high diversity index (0.9947 and 0.9267, respectively), highlighting a high discriminatory power, superior to that of both capsular typing and MLST (diversity index of 0.9017 for MLST). This method has the advantage of being correlated with MLST (through analysis of the terminal direct repeat and ancestral spacers), and to possess a high discriminatory power (through analysis of the leader-end spacers recently acquired which are the witnesses of genetic mobile elements encountered by the bacteria). Furthermore, this “one-shot” approach presents the benefit of much-reduced time and cost in comparison with MLST. On the basis of these data, we propose that this method could become a reference method for GBS typing.